Foundations of site selection procedures for deep geological repositories: an argument-based model to explain how site rejection decisions can be justified by inaccurate operationalizations and assessments of long-term protection - Navarro, Martin (Frontiers in Nuclear Engineering, 2025)
Site selection procedures for deep geological repositories are driven by the rejection of candidate sites whose degree of long-term protection is insufficient or less sufficient. If long-term protection is defined in relation to future exposures, it has to be operationalized, that is, translated into measurable indicators, such as dose or degree of containment, which, again, have to be evaluated by safety assessments. Site selection procedures, therefore, depend on the quality with which long-term protection is operationalized and assessed. Although it is widely acknowledged that operationalizations and assessments of long-term protection are inherently inaccurate, little attention has been paid to the question whether these inaccuracies prevent site selection procedures from improving long-term protection. Still, there is no theory of site selection that could specify the conditions under which site selection procedures are rational with regard to the target of long-term protection. To contribute to such a theory, a conceptual model is presented that explores how site rejection decisions can be justified by inaccurate operationalizations and safety assessments. The model rests on the assumption that site rejections are justified by logical arguments. By explicating what is needed to support the arguments, the model displays the complex structure of the justification, which, amongst others, rests on the quality of operationalization, safety assessment and system understanding. The presented argument-based approach is novel in the context of site selection. However, it is not meant as an alternative to multi-criteria decision-making, but as a necessary complement to understand the potential and limitations of safety-related decision criteria. The presented model identifies which types of errors are tolerable in the context of site selection and it explains why error tolerance is lowest for safety comparisons. The model points out that the frequently used assessment strategy of conservatism is not suitable for rejecting sites for reasons of insufficient or lower safety. It also shows that consensual requirements for the conditions under which long-term protection is achieved may be powerful tools for site selection.